An Analytical Review on Water Resources and Their Management: Issues and Challenges: Understanding the Water Crisis in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
India, with a population of over a billion is the world's biggest majority rules system, generally, progress in India as around the globe have to a great extent advanced and created around water bodies as most human exercises, including agriculture and industry rely upon water. The water circumstance in India is by all accounts going from awful to more terrible. Not exclusively is there a developing shortage of water in the nation, the agriculturally imperative states like Punjab, Haryana, Tamilnadu and Rajasthan are confronting an enduring fall in their ground water levels. While the per capita accessibility of utilizable water in India in 1951 was 3,450 cubic meters in 1999 it boiled down to 1,250 cubic meters. This as indicated by the Ministry of Water Resource is relied upon to diminish to 662 cubic meters for each individual in 2050. This paper endeavors to centers around water asset of India. A scene of dispersion, patterns of quality change, use, abuse and management strategies. The most recent couple of decades have seen emotional ascent in the interest for water in India because of an assortment of financial procedures and demographic patterns. Supplies have additionally developed complex, to keep pace with the interest through abuse of surface and groundwater. The outcome groundwater resources are over-misused in numerous parched and semiarid locales, prompting falling water levels, decaying groundwater quality causing groundwater shortage. Surface water resources are over-appropriated in numerous bowls. Surface supplies are quick draining because of siltation. Freshwater supplies are progressively going under danger of contamination from industrial effluents and municipal waste. Challenges to advancing feasible, fair and proficient management of India's water resources are a few. To begin with, the non-accessibility of satisfactory logical information on amount and quality of water, interest for water in various sectors, nature and degree and reasons for water issues become significant preventions to creating economical water management strategies